CDH1-involved Ubiquitination of SIRT5 Promotes the Entry of Colorectal Cancer Cells into Quiescence and Enhances Cell Stemness - Li, Wei; Chen, Jian; Yang, Jinbao; Zhang, Bo; Wen, Dihao; Jiang, Zhibin (Anti-Cancer Agents in Medicinal Chemistry, 2025)
BackgroundThis study explored whether the cell cycle regulator cadherin 1 (CDH1) impacts colorectal cancer cell cycle and stemness via mediating ubiquitination of sirtuin 5 (SIRT5).MethodsWe first constructed CDH1 overexpression plasmid and small interfering RNA against SIRT5 (siSIRT5) and transfected them into HCT116/HT29 cells, followed by transfection efficiency verification. The effect of CDH1 on Cyclin F/SIRT5/CDH1 protein levels in HCT116/HT29 cells was verified by Western blot. After up-regulation of CDH1, changes in SIRT5 ubiquitination (immunoprecipitation), cell cycle (cell cycle kit), proliferation (5-Bromodeoxyuridine assay), and stemness marker expressions (qRT-PCR) in HCT116/HT29 cells were detected. Rescue assays were performed to examine cell proliferation and stemness marker expressions.ResultsOverexpression of CDH1 decreased Cyclin F expression and increased SIRT5 and CDH1 expressions in HCT116/HT29 cells. Up-regulation of CDH1 suppressed SIRT5 ubiquitination, promoted G0/G1 phase blockage in HCT116/HT29 cells, boosted cell proliferation into quiescence and enhanced cell stemness. siSIRT5 counteracted the regulatory effect of CDH1 overexpression on colorectal cancer cells.ConclusionCDH1 promotes the entry of colorectal cancer cells into quiescence and enhances stemness by dampening SIRT5 ubiquitination.
Keywords: sirtuin 5